Long-term Monitoring Gait Analysis Using a Wearable Device in Daily Lives of Patients with Parkinson’s Disease: The Efficacy of Selegiline Hydrochloride for Gait Disturbance - Iijima, Mutsumi; Mitoma, Hiroshi; Uchiyama, Shinichiro; Kitagawa, Kazuo (Frontiers in Neurology, 2017)
Objective: The aim of this study was to assess quantitatively the gait disorders in the daily lives of patients with Parkinson’s disease (PD) using with a newly developed portable gait rhythmogram (PGR), which has a trunk-mounted acceleration sensor and automatic gait-detection algorithm. Methods: Using the PGR, we recorded the daily walking profiles of 14 PD patients before and after the addition or increase in dose of an MAO-B inhibitor (selegiline, average dose: 4.0 mg/day) as part of their medicine regimen, and evaluated their gait using the unified Parkinson's disease rating scale (UPDRS) and scores from a freezing of gait (FOG) questionnaire. Results: Before treatment with selegiline, the overall movements per 24 h was decreased below 0.41 m/s2 [mean –1.5 standard deviation (SD)] in 8 patients. The mean gait acceleration was decreased below 1.94 m/s2 (mean –2 SD) in 10 patients. The slope of the linear regression line was increased to 1.6 (mean +1.5 SD) in 8 patients. The cadence was increased to 124 steps/min (mean +1.5 SD) in 4 patients. Based on continuous PGR recordings in the daily lives of the patients for 24 h, the addition or increase in dose of selegiline increased the amplitudes of gait accelerations in 4 of 10 patients (40.0%), widened the range of gait accelerations in 5 of 8 patients (62.5%), diminished the cadence in 4 of 4 patients (100%), and diminished the fluctuations in gait throughout the day in 12 of 14 patients (85.7%). The UPDRS III and FOG scores significantly improved after the addition or increase in dose of selegiline (p < 0.005, p < 0.01, respectively). However, changes in gait-related scores of UPDRS were not detected in 6 patients. Conclusion: Improvements in the gait fluctuations of PD patients after the addition or increase in dose of selegiline were detected using the PGR in the daily lives of the patients for 24 h. The PGR had a higher sensitivity for detecting the improvements than UPDRS scores.